2004
DOI: 10.1113/jphysiol.2003.048777
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the excitability of human motor cortex with premotor rTMS

Abstract: Recent studies have shown that low-frequency repetitive transcranial magnetic stimulation (rTMS) to the left dorsal premotor cortex has a lasting influence on the excitability of specific neuronal subpopulations in the ipsilateral primary motor hand area (M1 HAND ). Here we asked how these premotor to motor interactions are shaped by the intensity and frequency of rTMS and the orientation of the stimulating coil. We confirmed that premotor rTMS at 1 Hz and an intensity of 90% active motor threshold (AMT) produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
126
4
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(149 citation statements)
references
References 32 publications
16
126
4
3
Order By: Relevance
“…Such an effect was not found after rTMS applied over the PMC (Experiment 2, Figure 3B) whereas only a trend toward suppression was found after rTMS over the primary motor cortex (Experiment 3, Figure 3C). Although the suppression of cortico-spinal excitability following low-rate rTMS of the motor cortex in Experiment 3 is consistent with other observations (Chen et al, 1997;Hallett, 2000;Maeda, Keenan, Tormos, Topka, & PascualLeone, 2000b;Pascual-Leone et al, 1999Rothwell, 1991;Walsh & Cowey, 2000) the lack of similar effects in Experiment 2 (when the rTMS was applied to the PMC) is surprising in light of findings that have shown the presence of a robust decrease of cortico-spinal excitability after 1 Hz rTMS to the PMC (Gerschlager, Siebner, & Rothwell, 2001) when intensities of 90% of motor threshold has been employed (Rizzo et al, 2003). Other studies employing low intensities of stimulation (80% MT) on the same premotor spot have shown small or no modulatory effects on MEP amplitude (Mü nchau, Bloem, Trimble, & Rothwell, 2002).…”
supporting
confidence: 79%
“…Such an effect was not found after rTMS applied over the PMC (Experiment 2, Figure 3B) whereas only a trend toward suppression was found after rTMS over the primary motor cortex (Experiment 3, Figure 3C). Although the suppression of cortico-spinal excitability following low-rate rTMS of the motor cortex in Experiment 3 is consistent with other observations (Chen et al, 1997;Hallett, 2000;Maeda, Keenan, Tormos, Topka, & PascualLeone, 2000b;Pascual-Leone et al, 1999Rothwell, 1991;Walsh & Cowey, 2000) the lack of similar effects in Experiment 2 (when the rTMS was applied to the PMC) is surprising in light of findings that have shown the presence of a robust decrease of cortico-spinal excitability after 1 Hz rTMS to the PMC (Gerschlager, Siebner, & Rothwell, 2001) when intensities of 90% of motor threshold has been employed (Rizzo et al, 2003). Other studies employing low intensities of stimulation (80% MT) on the same premotor spot have shown small or no modulatory effects on MEP amplitude (Mü nchau, Bloem, Trimble, & Rothwell, 2002).…”
supporting
confidence: 79%
“…However, because TMS of M1 can affect movement execution by inducing a muscle twitch, it was important to apply TMS after the movement was effectively over. Although stimulation at subthreshold intensity would prevent noticeable muscle twitch during movement, it could still affect the corticocortical and corticospinal circuit of the stimulated site (Rizzo et al, 2004), and thereby affect movement execution. We therefore required an adaptation task that, considering response latency of M1 to visual feedback (e.g., 112-192 ms) (Riehle, 1991) and to errors (e.g., 100 -150 ms after onset of reaching movement with force-field perturbations) (Green et al 2007), would allow a significant percentage of feedback to be received by M1 after the trial end.…”
Section: Discussionmentioning
confidence: 99%
“…The use of subthreshold intensity reduced the spread of stimulation away from the targeted site (Pascual-Leone et al, 1994;Gerschlager et al, 2001;Munchau et al, 2002). An intensity of 90% AMT was used according to the stimulation protocol known to produce robust increases in corticospinal excitability when delivered to the PMd (Rizzo et al, 2004).…”
Section: Rtmsmentioning
confidence: 99%
“…Physiological studies of the effects of "off-line" 5 Hz rTMS to motor (Peinemann et al, 2004) and dorsal premotor (Rizzo et al, 2004) cortices have shown that it induces efficient, long-lasting increases in neuronal excitability. By analogy with on-line "vir-tual" lesions caused by single-pulse TMS applied during task performance (Jahanshahi and Rothwell, 2000), we hypothesized that persistent effects of conditioning 5 Hz rTMS over dorsolateral prefrontal cortex (DLPFC) would alter behavioral performance and lead to changes in brain activity measured with functional magnetic resonance imaging (fMRI) in a variant of the original Posner paradigm in which subjects performed a cued visual choice reaction time (RT) task that required bimanual responses.…”
Section: Introductionmentioning
confidence: 99%